PENGEMBANGAN MEDIA KOMIK ELEKTRONIK BERBASIS POTENSI LAUT BENGKULU UNTUK MENINGKATKAN LITERASI KEMARITIMAN SISWA SD - Muktadir, Abdul; Gumono; Atika Susanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop an electronic comic-based learning media utilizing the marine potential of Bengkulu, designed to effectively improve maritime literacy among elementary school students. The research uses the Research and Development (R&D) method with the Borg and Gall model. The study subjects include material experts, presentation experts, teachers, and students. The validation results show that the electronic comic media is considered